Does occupational exposure to low-dose ionizing radiation induce cell membrane damage? - Đurović Branka 1; Selaković Vesna M.; Spasić-Jokić Vesna M. (Archive of Oncology, 2004)
BACKGROUND: Chronic exposure to low-dose radiation doses could be much more harmful than high, short-term doses because of lipid peroxidation initiated by free radicals. The cell membranes and cellular organelles are the main targets for free radicals attack. Peroxidation of cell membrane increases with decreasing dose rate (Petkau effect). The aim of this study was to establish if chronic occupational exposure to low-dose ionizing radiation could induce cell membrane damage. METHODS: Our investigation comprised 77 medical workers: 44 occupationally exposed to ionizing radiation (E), divided in two subgroups-exposed to x-rays (Ex) or gamma rays (En), and 33 controls (C). Informed consent and questionnaire containing dietary, habits, medical factors and exposure history were taken. Groups were matched in gender, age, dietary habits, alcohol consumption, smoking habit, and specific exposure time. Radiation dose accumulated by occupationally exposed over years was calculated on the basis of individual TL-dose records. Besides regular biochemical and cytogenetic tests, lipid peroxidation index, expressed as malondyaldehyde production was performed. RESULTS: Significantly higher lipid peroxidation index was found in workers occupationally exposed to low-dose of ionizing radiation (p>0.000028), which is correlated with age, smoking habit, and significantly correlated with doses. After blood samples in vitro irradiation by 2 Gy of gamma-radiation malondyaldehyde production significantly increased in each group, but were not significantly different between groups. CONCLUSION: Lipid peroxidation index could be considered as triage parameter for further cytogenetic studies in workers chronically exposed to low-dose radiation.